2017
DOI: 10.1007/s00216-017-0791-y
|View full text |Cite
|
Sign up to set email alerts
|

Development of a light-initiated chemiluminescent assay for the quantitation of sIgE against egg white allergens based on component-resolved diagnosis

Abstract: The determination of specific IgE (sIgE) level is of great importance in IgE-mediated food allergies. Our aim was to develop a homogeneous immunoassay-light-initiated chemiluminescent assay (LICA)-for measuring allergen sIgE of a single component in egg white, thus evaluating the LICA-sIgE assay as a useful tool in the diagnosis of food allergy. The LICA-sIgE assay was performed by incubating serum sample with anti-human IgE antibody coated with chemiluminescer beads, streptavidin-coated sensitizer beads, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…A bead-based light-initiated chemiluminescent assay (LICA) system was demonstrated in our previous studies to determine serum egg component-sIgE and sIgG4 profiles. LICA has been proven to have excellent analytical performances and a good correlation with Phadia Immu-noCAP tests in sIgE measurement [16,17]. Yet, only a limited profile of allergy tests has been introduced in our country; LICA could be a reliable complement in allergy screening and diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A bead-based light-initiated chemiluminescent assay (LICA) system was demonstrated in our previous studies to determine serum egg component-sIgE and sIgG4 profiles. LICA has been proven to have excellent analytical performances and a good correlation with Phadia Immu-noCAP tests in sIgE measurement [16,17]. Yet, only a limited profile of allergy tests has been introduced in our country; LICA could be a reliable complement in allergy screening and diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Samples with sIgE to egg white ≥ 0:35 kU A /L were defined as positive. [16,17]. The results of sIgE and sIgG4 were calculated as relative light units (RLU).…”
Section: Determination Of Total Ige and Egg-specific Ige Levelsmentioning
confidence: 99%
“…When the distance is within 200 nm, singlet oxygen will transfer from the donor beads to the acceptor beads under excitation, which will cause the acceptor beads to fluoresce at 520‐618 nm. This is a homogeneous method that is sensitive, specific, stable, and free of separation and washing steps and has high throughput . Because the concentration of E2 varies greatly in different periods, the detection method requires a large detection interval to meet the clinical needs.…”
Section: Introductionmentioning
confidence: 99%
“…The levels of sige and sigG 4 to rPen a 1 as well as its peptides were measured using a light-initiated chemiluminescent assay (lica) carried out as previously described (34,35). lica is based on the formation of nanoparticle pairs and luminescence oxygen channeling immunoassay technology (36,37).…”
Section: Preparation Of Biotinylated Recombinant Pen a 1 Ez-linkmentioning
confidence: 99%
“…lica is based on the formation of nanoparticle pairs and luminescence oxygen channeling immunoassay technology (36,37). Studies have shown that this new method possesses excellent performance characteristics with high sensitivity, broad analytical range and rapid turnaround cycles and is suitable for immunodetection of allergen sige and sigG 4 (34,35 well and incubated at 37˚C for 30 min with mild agitation. Subsequently, 150 µl streptavidin-coated sensibeads (Beyond Biotech, co., ltd.) were added.…”
Section: Preparation Of Biotinylated Recombinant Pen a 1 Ez-linkmentioning
confidence: 99%